2009
DOI: 10.1348/026151008x334728
|View full text |Cite
|
Sign up to set email alerts
|

Generativity and imagination in autism spectrum disorder: Evidence from individual differences in children's impossible entity drawings

Abstract: This study examined the cognitive underpinnings of spontaneous imagination in autism spectrum disorder (ASD) by way of individual differences. Children with ASD (N = 27) and matched typically developing (TD) children were administered Karmiloff-Smith's (1990) imaginative drawing task, along with measures that tapped specific executive functions (generativity, visuospatial planning, and central coherence processing style) and false belief theory of mind (ToM) understanding. The ASD group drawings displayed defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 39 publications
(129 reference statements)
2
39
0
Order By: Relevance
“…Several authors suggest that the so-called Von Economo neurons (VENs) are involved in the self-awareness (Evrard et al, 2012) hence it can be surmised that VENs play a role in imagination processes. In agreement with such a view alterations in VENs have been described in autistic patients (Santos et al, 2011) as well as an impoverishment of their imagination capabilities (Craig and Baron-Cohen, 1999; Low et al, 2009). …”
Section: Introductionmentioning
confidence: 53%
“…Several authors suggest that the so-called Von Economo neurons (VENs) are involved in the self-awareness (Evrard et al, 2012) hence it can be surmised that VENs play a role in imagination processes. In agreement with such a view alterations in VENs have been described in autistic patients (Santos et al, 2011) as well as an impoverishment of their imagination capabilities (Craig and Baron-Cohen, 1999; Low et al, 2009). …”
Section: Introductionmentioning
confidence: 53%
“…People who are diagnosed with such are described as having limitations in the areas of social cognition [21][22][23][24][25][26][27][28][29][30] and empathy [31][32][33][34][35]. Research has also identified a lack of enterprise and an inability to take the initiative amongst people who have been diagnosed with high-functioning autism [36,37], as well as a limited ability to make plans and to be flexible [24]. This research, however, has been challenged by studies that claim that poor results on all sorts of tests can be attributed to difficulties in understanding what psychiatrists and researchers expect from the high-functioning autistic subject, instead of any specific cognitive impairment(s) [38].…”
Section: High-functioning Autismmentioning
confidence: 99%
“…They need a "changeover period" [64] each time they complete one activity and move on to another before they are fully engaged in their studies. Whilst it may be the case that people with high-functioning autism are sometimes characterised as lacking flexibility [24] and lack an enterprising spirit and an ability to take the initiative [36,37], Folk High School's ability to interact with each participant on an individual level and to provide then with the necessary changeover period may be a contributing factor to the fact that participants feel less stress than during their previous schooling.…”
Section: Participant-centred Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a later workshop which did include design examples, the examples acted as scaffolds for more novel ideas that were also relevant to the educational objectives of the game. Furthermore the inclusion of design examples can be imperative for children who would otherwise be unable or face severe challenges to be able to participate within the design process (Benton et al, 2011;Hornof, 2009), for instance by providing scaffolding for children with autism who may struggle with the more abstract aspects of the creative process (Low et al, 2009).…”
Section: Pd Creativity and Design Examplesmentioning
confidence: 99%